2010
DOI: 10.1111/j.1552-6569.2008.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Voxel‐Based Morphometry and Voxel‐Based Relaxometry in Parkinsonian Variant of Multiple System Atrophy

Abstract: Diffuse brain atrophy, mainly in the motor circuitry is observed in MSA-P. Normalization for atrophy should always be performed in T2 measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 42 publications
2
14
1
1
Order By: Relevance
“…Voxel-based morphometry (VBM), an operator-independent automated method, can detect focal volume differences between 2 or more groups based on study-specific templates (Ashburner et al, 2000). Studies using this approach confirmed previous ROI-based volumetric studies suggesting basal ganglia, infratentorial as well as cortical volume loss in MSA patients (Minnerop et al, 2007; Moller et al, 2017; Specht et al, 2003; Tzarouchi et al, 2010). Moreover, specific longitudinal changes in MSA (early atrophy of basal ganglia followed by late cortical atrophy) have been identified with this technique (Brenneis et al, 2007).…”
Section: Brain and Cardiac Neuroimagingsupporting
confidence: 83%
“…Voxel-based morphometry (VBM), an operator-independent automated method, can detect focal volume differences between 2 or more groups based on study-specific templates (Ashburner et al, 2000). Studies using this approach confirmed previous ROI-based volumetric studies suggesting basal ganglia, infratentorial as well as cortical volume loss in MSA patients (Minnerop et al, 2007; Moller et al, 2017; Specht et al, 2003; Tzarouchi et al, 2010). Moreover, specific longitudinal changes in MSA (early atrophy of basal ganglia followed by late cortical atrophy) have been identified with this technique (Brenneis et al, 2007).…”
Section: Brain and Cardiac Neuroimagingsupporting
confidence: 83%
“…Putaminal atrophy in MSA was not significant compared to PD in our VBM analysis, but has been detected in previous VBM studies comparing MSA to controls [26,27,28] and MSA to PD [27]. Differences in disease duration and the limited size of our study population might be reasons for this discrepancy.…”
Section: Discussioncontrasting
confidence: 48%
“…ROIs were put on the “single_subj_T1.nii” image regarded as the anatomically standard image in SPM5, in the fourth ventricle, cerebellum hemisphere; these were derived from the WFU_PickAtlas, extension program of SPM5 [28, 29]. We also put ROIs on the “FMRIB58_FA-skeleton_1 mm.nii” image, which is the anatomically standard image in FSL, in the MCP, superior cerebellar peduncle (SCP), pons, substantia nigra, superior temporal white matter region, prefrontal white matter regions, and primary motor region where previous studies showed differences among the patients with MSA-C, MSA-P, PD, and controls (Figure 1) [20, 22, 3037]. The value of a particular tissue was extracted using the software MarsBar [38], an extension program of SPM5.…”
Section: Methodsmentioning
confidence: 99%